Existence of Bounded Solutions for a Class of Degenerate Fourth-Order Elliptic Equations with Convection Terms - Salvatore D’Asero (Mathematics)
This paper deals with the existence of bounded and locally Hölder continuous weak solutions of the following nonlinear fourth-order Dirichlet problem: <semantics><mstyle displaystyle="true"><munder>∑|α|=1,2</munder></mstyle>(−1)|α|Dα<mfenced separators="" open="[" close="]">Aα(x,u,D1u,D2u)−Eα(x) |u|λ(pα−1) signu</mfenced>=f</semantics> in <semantics>Ω</semantics>, where the coefficients <semantics>Aα</semantics> satisfy a strengthened degenerate coercivity condition.